2012
DOI: 10.1016/j.jconrel.2012.04.022
|View full text |Cite
|
Sign up to set email alerts
|

Minimizing acylation of peptides in PLGA microspheres

Abstract: The main objective of this study was to characterize and find mechanisms to prevent acylation of therapeutic peptides encapsulated in glucose-star poly(D,L-lactic-co-glycolic acid) (PLGA) microspheres. The effect of addition of divalent cation salts CaCl2, MnCl2 as well as carboxymethyl chitosan (CMCS) on inhibition of acylation of octreotide (Oct), salmon calcitonin (sCT), and human parathyroid hormone (hPTH) was evaluated. Peptide content and integrity inside the degrading microspheres was monitored by rever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 41 publications
3
39
0
Order By: Relevance
“…Nearly 60% of the octreotide was acylated and <20% of native octreotide was released during the In vitro release over a period of 3 months. Similar results has been reported for other peptides and proteins such as bovine serum albumin, human atrial natriuretic peptide, human parathyroid hormone, leuprolide, insulin and salmon calcitonin (Ghalanbor et al, 2012; Ibrahim et al, 2005; Lucke et al, 2002; Na et al, 2003b; Zhang and Schwendeman, 2012). …”
Section: Introductionsupporting
confidence: 87%
“…Nearly 60% of the octreotide was acylated and <20% of native octreotide was released during the In vitro release over a period of 3 months. Similar results has been reported for other peptides and proteins such as bovine serum albumin, human atrial natriuretic peptide, human parathyroid hormone, leuprolide, insulin and salmon calcitonin (Ghalanbor et al, 2012; Ibrahim et al, 2005; Lucke et al, 2002; Na et al, 2003b; Zhang and Schwendeman, 2012). …”
Section: Introductionsupporting
confidence: 87%
“…Moreover, the entire spectra of released IgG ranging from 200 to 250 nm were also identical to native IgG, suggesting retention of secondary conformation of IgG during NP preparation and release from NPs. Previous reports suggest that PLA-and/or PGA-based copolymer produces a large molar mass of lactic acid and/or glycolic acid (18,19). These degradation products can stimulate hydrolytic degradation of protein therapeutics.…”
Section: Secondary Structure Stability Estimation Of Iggmentioning
confidence: 99%
“…However, it is widely reported that protein and peptide can undergo loss of biological activity during formulation, storage, and/or release (12)(13)(14)(15). The presence of hydrophobic/hydrophilic interfaces (16), reduction in pH during polymer degradation (17), and degradation product (lactic acid and glycolic acid)-induced acylation processes (18,19) are potential sources of irreversible aggregation or inactivation of therapeutic proteins inside. The three-dimensional structure of protein is very important for its pharmacological activity.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, we sought to minimize the peptide–polymer interaction by outcompeting the peptide for the polymer carboxylates [44,116, 117]. By adding various water-soluble salts of divalent cations, such as Mn 2+ and Ca 2+ , to suspensions of acid-end group PLGA and the peptide, the octreotide–polymer interaction was strongly inhibited, resulting in a modest decrease in peptide acylation [44].…”
Section: Approaches To Overcome Issues Impeding Depot Developmentmentioning
confidence: 99%
“…This strategy also translated into sharp decreases in octreotide acylation when encapsulated in microspheres when formulation conditions were optimized [116]. The approach was found to be augmented in certain cases when carboxymethyl chitosan was added to the formulation to help retain the divalent cationic salts [117]. …”
Section: Approaches To Overcome Issues Impeding Depot Developmentmentioning
confidence: 99%